Cutibacterium species: An Underestimated Pathogen in Chronic Infections: Cuibacterium infection in chronic infection - Sharma, Bhawna; Upadhyaya, Gargi (Hasanuddin University, 2024)
Cutibacterium speciesis a member of the skin micro biota, found predominantly in regions rich in sebaceous glands, involved in various chronic infections that led to its emergence as an opportunistic pathogen. The present study is a retrospective study to determine the prevalence and antibiotic sensitivity pattern of Cutibacterium species recovered from chronic infections over a period of 4.5 years. The identification of the colonies grew on the Robertson’s Cooked Meat media plate was done using VITEK 2. The antibiotic sensitivity tests were put by pour plate method using Epsilometer strips (E-strip).Out of 400, 17.75% (n=71) were confirmed as anaerobic bacteria by VITEK 2. Out of 71 positive anaerobic organisms, 21% (n=15/71) were confirmed as Cutibacteriumspecies.Cutibacterium species recorded prevalenceof 3.75% (15/400) among clinical specimens. High sensitivity was observed with beta lactam group of drugs whereas metronidazole drug was found ineffective against Cutibacteriumspecies. Due to prolonged culture time for anaerobic bacteria there is a high need in new diagnostic methods. In the recent times Cutibacterium species has been reported from various clinical samples which depicts shift of Cutibacterium species as a potential pathogen in the upcoming time.